Synthesis and characterization of carbon based counter electrode for dye sensitized solar cells (DSSCs) using sugar free as a carbon material. (1st March 2017) - Kumar, Rahul; Nemala, Siva Sankar; Mallick, Sudhanshu; Bhargava, Parag
Graphical abstract: Highlights: Carbon material was produced from graphitization of sugar free at high temperature in flowing argon. The produced carbon material showed graphitic nature and electrocatalytic property. Counter electrode for DSSC was fabricated using the carbon material. Jsc, VOC and η of fabricated cell was 17.10 mA cm −2, 0.66 V and 6.72% respectively. Abstract: Dye sensitized solar cells (DSSCs) are a low cost alternative to silicon-based and thin film solar cells. Usually DSSCs utilize platinum to catalyze the iodine redox couple and complete the electric circuit. Though, platinum is an excellent catalytic material for use in preparation of counter electrodes (CEs) for DSSCs but it is expensive. Alternatives to replacement of platinum (Pt) that have been examined are carbon materials, conductive polymers. In this work, counter electrode for DSSCs was fabricated using carbon material obtained from carbonization of sugar free at high temperature. Slurry of the carbon produced by carbonization was made with polyvinylpyrrolidone (PVP) as a surfactant and a coating was obtained by doctor blading the slurry over the FTO glass substrate. The DSSCs based on produced carbon CE show a maximum power conversion efficiency of 6.72% (area 0.25 cm 2 ), which is comparable to 8.19% of the cell with the conventional Pt CE at the same experimental conditions. The current density (Jsc) and open circuit voltage (VOC ) of the DSSCs was 17.10 mA cm −2 and 0.66 V respectively.